PEMBUATAN TEPUNG MOCAF MELALUI PENAMBAHAN STARTER DAN LAMA FERMENTASI (Modified Cassava Flour) - Muhammad Iqbal Nusa; Budi Suarti; Alfiah , (AGRIUM: Jurnal Ilmu Pertanian, 2012)
This study aims to find ways of making mocaf  flour with a comparison of starter and a long fermentation on the quality of mocaf flour. This study uses a complete Randomized Design (CRD) factorial. The results of statistical analysis on  each parameter : The number of a long fermentation different effect not significant (p≥0.05) on moisture content. The number of different starter effect highly significant (p≤0.01) for yield, starch content, texture. The number of a long  fermentation different effect highly significant (p≤0.01) for yield, starch content, texture. The number of starter different effect not significant (p≥0.05) on moisture content. Treatment interaction effect is not significant (p≥0.05) for yield, content starch, texture and moisture content.Keywords : Manihot esculenta, mocaf, starter, fermentation